Investigation of West Nile virus in central nervous system infections of unknown etiology in Ankara, Turkey - Ergünay, Koray; Aydoğan, Sibel; Menemenlioğlu, Dilek; Sener, Burçin; Lederer, Sabine; Steinhagen, Katja; Hasçelik, Gülşen; Pinar, Ahmet; Ozkul, Aykut; Us, Dürdal (Mikrobiyoloji bülteni, 2010)
Arthropod-borne viral infections have recently gained considerable attention and importance as re-emerging infections in a global scale. West Nile Virus (WNV), a member of Flaviviridae, is an enveloped positive strand RNA virus that is usually transmitted to humans by the bite of Culicine mosquitoes. Although the majority of the human infections are asymptomatic, WNV may also cause febrile and neuro-invasive diseases. Seroprevalence data from Turkey indicate that WNV activity is present in Central Anatolia. In this study performed at Hacettepe University Hospital, paired serum and cerebrospinal fluid (CSF) samples from 87 adult patients with the preliminary diagnosis of aseptic meningitis/encephalitis of unknown etiology were evaluated retrospectively to identify WNV-related syndromes. Bacterial, fungal and mycobacterial cultures yielded negative results and Mycobacterium tuberculosis and Herpes simplex virus nucleic acid tests were also negative for the selected patients. Commercial enzyme-linked immunosorbent assay (ELISA)s and indirect immunofluorescence test (IIFT)s were employed for WNV IgM and IgG antibody detection (Anti-WNV Virus IgG/IgM ELISA, Anti-WNV Virus IgG/IgM IIFT; Euroimmun, Germany). Additional ELISA/IIFT assays were further performed for WNV antibody reactive samples to identify cross-reactions and/or infections with other flaviviruses and phleboviruses. All WNV antibody positive samples were also evaluated by a WNV real-time reverse-transcription polymerase chain reaction (RT-PCR) assay. WNV IgM and IgG antibodies were detected in %9.2 (8/87) and 3.4% (3/87) of the serum samples, respectively. All IgG reactive samples were negative for IgM. All sera with WNV antibody reactivity (n = 11) and the corresponding CSF samples were negative for viral RNA via RT-PCR. In 5 of the 8 WNV IgM positive subjects, sandfly fever virus IgM antibodies were detected, which was also accompanied by Dengue virus IgM positivity in one sample. In another case, intrathecal antibody synthesis against measles virus was demonstrated. Two cases (2/87; 2.3%) with WNV IgM positivity as the only serologic marker were identified as probable WNV infections and clinical features were discussed. In conclusion, in order to fully understand the impact of WNV and/or other flavivirus infections in Turkey, epidemiology and ecological features of these agents need to established.